Characterization of eukaryotic microbial diversity in hypersaline Lake Tyrrell, Australia - Heidelberg, Karla B.; Nelson, William C.; Holm, Johanna B.; Eisenkolb, Nadine; Andrade, Karen; Emerson, Joanne B. (Frontiers in Microbiology, 2013)
This study describes the community structure of the microbial eukaryotic community from hypersaline Lake Tyrrell, Australia, using near full length 18S rRNA sequences. Water samples were taken in both summer and winter over a four year period. The extent of eukaryotic diversity detected was low, with only 35 unique phylotypes using a 97% sequence similarity threshold. The water samples were dominated (91%) by a novel cluster of the Alveolate, Apicomplexa Colpodella spp., most closely related to C. edax. The Chlorophyte, Dunaliella spp. accounted for less than 35% of water column samples. However, the eukaryotic community entrained in a salt crust sample was vastly different and was dominated (83%) by the Dunaliella spp. The patterns described here represent the first observation of microbial eukaryotic dynamics in this system and provide a multiyear comparison of community composition by season. The lack of expected seasonal distribution in eukaryotic communities paired with abundant nanoflagellates suggests that grazing may significantly structure microbial eukaryotic communities in this system.